2014
DOI: 10.1002/glia.22714
|View full text |Cite
|
Sign up to set email alerts
|

Mesenchymal stem cells induce the ramification of microglia via the small RhoGTPases Cdc42 and Rac1

Abstract: Activated microglia play a central role in the course of neurodegenerative diseases as they secrete cytotoxic substances which lead to neuronal cell death. Understanding the mechanisms that drive activation of microglia is essential to reverse this phenotype and to protect from neurodegeneration. With some exceptions, evidence indicates that changes in cell morphology from a star shape to a round and flat shape accompany the process of activation in microglia. In this study, we investigated the effect of adipo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
66
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 45 publications
(72 citation statements)
references
References 41 publications
5
66
1
Order By: Relevance
“…6 J-L). Since in our previous study we detected an extremely low number of infiltrated leukocytes in BCCAo model [27], these cells are likely to be migrating microglia [30,31]. Counting of these CD45…”
Section: Nfkb1 Deficiency Strongly Reduced Bccao-induced Microgliosismentioning
confidence: 93%
“…6 J-L). Since in our previous study we detected an extremely low number of infiltrated leukocytes in BCCAo model [27], these cells are likely to be migrating microglia [30,31]. Counting of these CD45…”
Section: Nfkb1 Deficiency Strongly Reduced Bccao-induced Microgliosismentioning
confidence: 93%
“…The activation of microglial cells, which are the resident macrophages of the central nervous system, occurs in concert with distinct morphological changes 55 . It was subsequently shown that soluble factors secreted by adipose-tissue-derived mesenchymal stem cells (ASCs) lead to elongated cell shape in microglia, which is also accompanied by a noninflammatory phenotype characterized by low TNF-α and IL-6, and high arginase-I production 56 (Fig. 3B).…”
Section: Cell Shapementioning
confidence: 99%
“…53,56 B) Immunofluorescence images of CD11b expression in microglia cells exposed to medium conditioned (CM) by mesenchymal stem cells and/or LPS (top), and their secretion of IL-6 and TNF-α and expression of arginase-1 (bottom). Scale bar = 10 μm.…”
Section: Figurementioning
confidence: 99%
See 1 more Smart Citation
“…Following these seminal studies, the immunomodulatory effects of MSCs on circulating adaptive, as well as innate, immune cells have been extensively studied [13][14][15][16][17][18][19][20][21][22][23][24][25][26][27][28][29]. In vitro, MSCs affect also the behavior of CNS cells such as microglial cells, and particularly inhibit microglial proliferation and their release of proinflammatory molecules; more specifically, MSCs induce the release of neuroprotective molecules by microglia and increase their phagocytic capability through the release of soluble factors [30][31][32][33][34][35]. Similarly, MSCs are able to skew the phenotype of macrophages from M1 to M2 type [36] [37].…”
Section: Introductionmentioning
confidence: 99%